PENGARUH 7 JENIS TEGAKAN HUTAN TANAMAN TERHADAP PRODUKTIVITAS SERTA NUTRISI RUMPUT RAJA DAN KANDUNGAN HARA TANAH DI WANAGAMA I, YOGYAKARTA - , Indah Riadi putri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The distribution of Raja grass, especially in the beds 17 and 18 of the education forest Wanagama I, Banaran Village, Playen Subdistrict, Gunung Kidul Dictrict, might be found under 7 species of plantation forest stands, which were teak (Tectona grandis), Acacia mangium (A. mangium), Mimba (Azadirachta indica), Acacia aulacocarpa (A. aulokokarpa), Kayu Putih (Melaleuca leucadendra), eucalyptus (Eucalyptus pellita), and Gamal (Gliricidia sepium). Though there have been many studies of various species of grass grooving in various places, the information of the production and the quality of Raja grass in the condition under different plantation forest stands was still highly limited. The study aimed at evaluating the condition of the place where the green fodder of Raja grass for livestock, the productivity and the quality of the green fodder grown under various species of plantation forest stands of Wanagama I in wet and dry seasons. The study was conducted by preparing study plots of 1 x 1 m2 under the 7 species of the stands with 2 repetitions that there are 14 plots per season. The results of the study showed that the best place in wet season was under the stands of Akasia aulococarpa with the sunlight intensity of 175.36 â 193.93 foot candle, the mean atmospheric and soil temperatures are 33.97Â°C â 37.30Â°C and 26.50Â°C â 30.57Â°, respectively, the mean atmospheric and soil humidity are 49.40% â 53.86% and 48.62% â 54.36%, the mean pH of 6.53 â 6.87 and the soil texture elements of sand, dust and clay were 28%-54%, 20%-23% and 23%-50%, the organic C content of 2.64% - 4.33%, the total N content of 0.19% - 0.27%, the total P2O5, K2O, Ca, Mg, Na, Fe, Mn, Zn and Cu contents were 13-21 mg/100 g, 22-26 mg/100 g, 345-448 mg/100 g, 87- 141 mg/100 g, 37-48 mg/100g,